1976
DOI: 10.1073/pnas.73.11.3825
|View full text |Cite
|
Sign up to set email alerts
|

Role of proteolytic enzymes in biological regulation (a review).

Abstract: Many enzymes, hormones, and other physiologically active proteins are synthesized as inactive precursors (zymogens) that are subsequently converted to the active form by the selective enzymatic cleavage (limited proteolysis) of peptide bonds. The ultimate agency of activating enzymatic function is limited proteolysis, either in a single activation step or in a consecutive series (cascade). The specificity of each activation reaction is determined by the complementarity of the zymogen substrate and the active s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
204
0
3

Year Published

1978
1978
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 386 publications
(209 citation statements)
references
References 54 publications
1
204
0
3
Order By: Relevance
“…In this study, it was observed that the enzyme treatment liberated the eggs by actually breaking down and removing the outer gum layer surrounding the eggs suggesting that higher hatch rates may arise from treated eggs that have less of a barrier surrounding the chorion to break through. The breakdown of the adhesive gum layer was an expected result because the general chemical function of proteolytic enzymes is to digest or breakdown the long chain molecules into amino acids (Neurath & Walsh, 1976). However, the mechanism by which the gum layer removal occurred was both interesting and unexpected; as enzyme exposure progressed, the gum layer started to swell and become less structured and instead of breaking down or dissolving into pieces the gum layer swelled until it was completely bloated, then came off as a single casing, leaving a clean non-adhesive egg.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was observed that the enzyme treatment liberated the eggs by actually breaking down and removing the outer gum layer surrounding the eggs suggesting that higher hatch rates may arise from treated eggs that have less of a barrier surrounding the chorion to break through. The breakdown of the adhesive gum layer was an expected result because the general chemical function of proteolytic enzymes is to digest or breakdown the long chain molecules into amino acids (Neurath & Walsh, 1976). However, the mechanism by which the gum layer removal occurred was both interesting and unexpected; as enzyme exposure progressed, the gum layer started to swell and become less structured and instead of breaking down or dissolving into pieces the gum layer swelled until it was completely bloated, then came off as a single casing, leaving a clean non-adhesive egg.…”
Section: Discussionmentioning
confidence: 99%
“…Several zymogens, e.g. chymotrypsinogen, have been shown to be activated by a proteolytic cleavage of internal peptide bonds located between two disulfide bridges, such that the active species comprises two peptide chains linked by disulfide bridges (145) and this could similarly account for the existence of two peptide chains in the serine carboxypeptidases from plants. The existence of only a single peptide chain in the active enzymes from fungi suggests that potential zymogens of these enzymes might be activated by cleavage of an internal peptide bond located on the N-terminal side of the disulfide bridges.…”
Section: Physico-chemical Properties Of Serine Carboxypeptidasesmentioning
confidence: 99%
“…Proteolytic processing is modulated both temporally and positionally and contributes to protein activation and sub-cellular localization [6]. Proteases involved in maturation of secretory proteins typically reside in the Trans-Golgi Network (TGN) where they proteolytically process newly formed proteins from the endoplasmic reticulum before packaging into secretory vesicles.…”
Section: Introductionmentioning
confidence: 99%